Analisis Komparatif Online Custo Analisis komparatif online customer review dan survey customer review marketing mix - Hilmy Mu’nis; Rita Komaladewi (Jurnal Ekonomi Modernisasi, 2019)
The purpose of this study is to compare between online customer review and customer review survey also to see the performance mapping of culinary tourism in Bandung using 4A marketing mix namely acceptability, affordability, accessibility and awareness with comparative and descriptive methods. This study uses Mann Whitney on SPSS and Spider Web Chart. Online tracking on Google Review and survey questionnaire are used as a measurement to get 100 customer review online assessments and 125 customer review survey assessments. Based on research results there is a difference between marketing mix 4A online customer results Google review and marketing mix 4A customer review survey results. This is marked from the 3 sub-variables used in this study, namely acceptability (taste, portion, aroma), affordability (price, price: taste, price: portion) and accessibility (atmosphere, cleanliness, service), there are differences in the results of the assessment in sub accessibility variable (atmosphere and service). Then, the results of mapping the performance of culinary tourism in the city of Bandung both online customer reviews and customer surveys have good performance for sub-variables acceptability (taste, portion, aroma) and affordability (price, price: taste, price: portion) but need improvement in the sub accessibility variables (suansana, cleanliness, service).